Voices and Bodies in the Play Carnes tolendas. Retrato escénico de una travesti: Scenes of Equality in Contemporary Argentinean Theatre - Marin, Fwala-lo (2023)
This paper explores the play Carnes tolendas. Retrato escénico de una travesti, starring the award-winning Argentinean actress and writer Camila Sosa Villada and directed by María Palacios. From the perspective of Theatre Studies, we analyze the possibility of the play to produce scenes of equality in terms of Jacques Rancière (2010; 2012). For this purpose, we observe how the performance is part of the crisis of the character (Ryngaert, 2013) in virtue of the fact that the construction of the staging consists on multiple textualities that are identified and reconstructed. We delve into the description and analysis of the construction of voices (Jolly and Moreira da Silva, 2013) and corporealities (Fischer-Lichte, 2011) that stage different materials, including dramatic texts, songs, biographical accounts and openings for dialogue with the audience.  On stage, Sosa Villada summons numerous bodies: the bodies of violent men from the family and police universe, the bodies of fragile women, the broken and worn bodies of García Lorca's women, her own trans body and even her own old body. The stage constructs and deconstructs representations of bodies and voices in the rhapsodic logic that stitches fragments together in contemporary theatre.  The dramaturgy of the stage opens up the possibility for spectators to go through an experience that gives voice to an invisible history and to be dazzled by the poetic capacities of the performer.